Electrocaloric effect at special points in the composition-temperature-electric field phase diagram of barium zirconate-titanate (BZT). Issue 5 (May 2023) - Novak, Nikola; Weyland, Florian; Khakpash, Nasser; Rossetti, George A.
Abstract: The composition-temperature-electric field diagram and electrocaloric properties of BaTi1−x Zrx O3 (BZT) were computed using a self-consistent phenomenological approach. By subtracting contributions from the latent heat, the adiabatic temperature change due solely to the material polarization was quantified on passing through critical end, tricritical and phase convergence points. The largest temperature change occurs at the first-order paraelectric to ferroelectric transitions where the latent heat is triggered, but the material polarization contribution is greatest at the critical temperature. The maximum electrocaloric responsivity occurs at a field 1.25 times greater than the critical field. The temperature change increases at the tricritical point due to a field-induced tetragonal to rhombohedral transformation, but the responsivity diverges due to vanishing of the critical field. The enhanced temperature change observed experimentally near the convergence point is attributed to greater polarization change in the rhombohedral phase, and to a polar glasslike state that contributes to the dipolar configurational entropy.